Penentuan Materi Layanan Bimbingan TIK Menggunakan Algoritma C4.5 - Montesna; Yuhandri; Jufriadif Na’am (Jurnal KomtekInfo, 2019)
Changes in curriculum from KTSP (Education Unit Level Curriculum) to 2013 Curriculum result in changes in Information and Computer Technology (ICT) subjects to ICT Guidance (BTIK). These subjects are not scheduled in general, so students need to be guided by questionnaires. To find out the right guidance needs data mining is needed. So this research is done in determining the accuracy of the guidance needs in accelerating the process of questionnaire data. The method used is C4.5 Algorithm. The results of the study have an accuracy of 90%, so it can be recommended in determining guidance material for students.